2013
DOI: 10.4028/www.scientific.net/amm.357-360.939
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of Freeze-Thaw on the Carbonation Property of Fly Ash Concrete

Abstract: Based on the coupling testing program of freeze-thaw and carbonation, the laboratory simulation test is carried out. The laws of carbonation depth of the fly ash concrete suffered the freeze-thaw cycle in different test modes and the influence of fly ash dosage on concrete carbonation depth after the freeze-thaw cycle are studied. Defining the influence coefficient of the freeze-thaw cycles on carbonation depth of concrete, the mechanism of coupling of freeze-thaw and carbonation is analyzed,and the role of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The experimental data adopted to establish the probabilistic prediction model of concrete carbonation depth in this paper are all collected from the references (i.e., Tables A1–A6), 21–35 and these experimental data are obtained from the accelerated carbonation tests in accordance with the China Standard (GB/T 50082) 36 . In these accelerated carbonation tests in the references, 21–35 the temperature in the accelerated carbonation chamber was controlled within (20 ± 5) °C, the relative humidity was controlled within (70 ± 5) %, and the CO 2 concentration was within (20 ± 3) %. Due to the temperature, relative humidity, and the CO 2 concentration of the accelerated carbonation tests in the references 21–35 are approximately identical, the probabilistic prediction model of carbonation depth in this paper only considers other factors affecting carbonation, including water‐binder ratio R wb , fly ash content R FA , concrete stress level δ , and carbonation time t .…”
Section: Influence Factors Of Carbonation Depthmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental data adopted to establish the probabilistic prediction model of concrete carbonation depth in this paper are all collected from the references (i.e., Tables A1–A6), 21–35 and these experimental data are obtained from the accelerated carbonation tests in accordance with the China Standard (GB/T 50082) 36 . In these accelerated carbonation tests in the references, 21–35 the temperature in the accelerated carbonation chamber was controlled within (20 ± 5) °C, the relative humidity was controlled within (70 ± 5) %, and the CO 2 concentration was within (20 ± 3) %. Due to the temperature, relative humidity, and the CO 2 concentration of the accelerated carbonation tests in the references 21–35 are approximately identical, the probabilistic prediction model of carbonation depth in this paper only considers other factors affecting carbonation, including water‐binder ratio R wb , fly ash content R FA , concrete stress level δ , and carbonation time t .…”
Section: Influence Factors Of Carbonation Depthmentioning
confidence: 99%
“…The main reason is that, with the increase of the tensile stress level, the microcracks inside the concrete continue to extend, and new cracks continue to generate, which provides more channels for the diffusion of CO 2 inside concrete, leading to the increase of carbonation depth. Relevant studies found that the relationship between carbonation depth and tensile stress level could be approximately described by linear function, 6,11,15,46 quadratic polynomial function, 33,47 exponential function, 48 and so forth. It can be concluded that, compared with other functions, the linear function is widely adopted.…”
Section: Influence Factors Of Carbonation Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…e effect of the freeze-thaw cycle on concrete carbonation is analysed by studying the neutralisation depth under alternate freezethaw cycles and carbonation as well as the test results of neutralisation depth in the single carbonation mode. e influence coefficient (λ F ) of the freeze-thaw cycle on the neutralisation depth of the concrete is introduced, which is expressed as follows [13]:…”
Section: Influence Coefficient Of the Freeze-aw Cycle On The Developmmentioning
confidence: 99%
“…erefore, in the design of concrete materials, alternate deteriorations caused by multiple factors should be considered. Hitherto, some preliminary and fragmentary studies have been performed to study the combined effect of freeze-thaw and carbonation on ordinary concrete and fly ash concrete [11][12][13][14][15]. Because research into concrete with fly ash as fine aggregate is restricted to the mechanical properties or effect of a single factor [16][17][18][19][20], conclusions of studies under single-factor conditions are limited.…”
Section: Introductionmentioning
confidence: 99%